THE CONCEPTUAL ROLE OF THE SHADOW ECONOMY IN ECONOMIC GROWTH - Юрій Коляда; Сергій Позняк (Економіка та суспільство)
The article examines the conceptual role of the shadow and gray economies in economic growth and substantiates the need to take them into account in multifactor models of economic development. The general division of the economy into white (official), gray and shadow economies, their characteristics and peculiarities of influence on macroeconomic indicators are considered. The official economy operates within the framework of the law, provides tax revenues, promotes employment growth and investment attractiveness. The gray economy, although not illegal, partially escapes state control, which leads to tax evasion and distortion of economic processes. The shadow economy encompasses illegal activities that may contribute to the short-term survival of a business, but in the long run undermine economic stability. It is proposed to include indicators of the shadow and gray economies in multivariate economic growth models to increase the degree of adaptability of the models and to make more accurate forecasts. In economic growth models, the gray economy is taken into account by adjusting the savings parameters, while the shadow economy requires the introduction of a separate capital intensity equation based on its own production function. To correctly reflect its impact, expressions describing shadow savings and investment are added to the equation of aggregate savings.